Prognostic Value of Late Gadolinium Enhancement for the Prediction of Cardiovascular Outcomes in Dilated Cardiomyopathy: An International, Multi-Institutional Study of the MINICOR Group. (April 2020) - Alba, Ana Carolina; Gaztañaga, Juan; Foroutan, Farid; Thavendiranathan, Paaladinesh; Merlo, Marco; Alonso-Rodriguez, David; Vallejo-García, Victor; Vidal-Perez, Rafael; Corros-Vicente, Cecilia; Barreiro-Pérez, Manuel; Pazos-López, Pablo; Perez-David, Esther; et al.
Abstract : Background: Dilated cardiomyopathy is associated with increased risk of major cardiovascular events. Late gadolinium enhancement (LGE) cardiac magnetic resonance imaging is a unique tissue-based marker that, in single-center studies, suggests strong prognostic value. We retrospectively studied associations between LGE presence and adverse cardiovascular events in patients with dilated cardiomyopathy in a multicenter setting as part of an emerging global consortium (MINICOR [Multi-Modal International Cardiovascular Outcomes Registry]). Methods: Consecutive patients with dilated cardiomyopathy referred for cardiac magnetic resonance (2000–2017) at 12 institutions in 4 countries were studied. Using multivariable Cox proportional hazard and semiparametric Fine and Gray models, we evaluated the association between LGE and the composite primary end point of all-cause mortality, heart transplantation, or left ventricular assist device implant and a secondary arrhythmic end point of sudden cardiac death or appropriate implantable cardioverter-defibrillator shock. Results: We studied 1672 patients, mean age 56±14 years (29% female), left ventricular ejection fraction 33±11%, and 25% having New York Heart Association class III to IV; 650 patients (39%) had LGE. During 2.3 years (interquartile range, 1.0–4.3) follow-up, 160 patients experienced the primary end point, and 88 experienced the arrhythmic end point. In multivariable analyses, LGE was associated with 1.5-fold (hazard ratio, 1.45 [95% CI, 1.03–2.04]) risk of the primary end point and 1.8-fold (hazard ratio, 1.82 [95% CI, 1.20–3.06]) risk of the arrhythmic end point. Primary end point risk was increased in patients with multiple LGE patterns, although arrhythmic risk was higher among patients receiving primary prevention implantable cardioverter-defibrillator and widening QRS. Conclusions: In this large multinational study of patients with dilated cardiomyopathy, the presence of LGE showed strong prognostic value for identification of high-risk patients. Randomized controlled trials evaluating LGE-based care management strategies are warranted. Abstract : Supplemental Digital Content is available in the text.